Cation ordering/disordering effects upon photocatalytic activity of CrNbO4, CrTaO4, Sr2CrNbO6 and Sr2CrTaO6. (21st January 2016) - Lv, Meilin; Ni, Shuang; Wang, Zhuo; Cao, Tongcheng; Xu, Xiaoxiang
Abstract: Doping has generally been served as one of the most efficient strategies for the improvement of wide band gap semiconductor photocatalysts. However, atomic arrangements of doped elements in the host crystal structure have often been overlooked, particularly during the investigation and evaluation of dopant functionality. It is known that electronic structures of a semiconductor are profoundly controlled by atomic occupancies in different crystallographic positions. Knowledge about dopant accommodations in the crystal structure and their influence towards photocatalytic performance is highly desired. Here, we investigated four compositional and structural relevant compounds CrNbO4, CrTaO4, Sr2 CrNbO6 and Sr2 CrTaO6 with the aim to study the effects of cation ordering/disordering upon their photocatalytic activity. Our results showed that ordered cations, namely Cr and Nb/Ta, are detrimental to the photocatalytic performance. Theoretical calculations indicate that cation ordering would enlarge the band gap and inhibit charge transfer between Cr and Nb/Ta. Our findings imply that ordered dopants in photocatalytic materials would severely offset the benefits of doping and might be a reason for the decreased activity at high doping levels often encountered. Graphical abstract: Ordering of the B-site cations in Sr2 CrNbO6 and Sr2 CrTaO6 will shift the band edges of conduction band and valence band, resulting in a significant widening of the band gaps, which blue-shifts the absorption edge. Highlights: Dopant ordering/disordering could be the reason for the optimal doping content. Dopant ordering will cause blue shift of optical absorption by enlarging band gaps. Dopant ordering is detrimental for photocatalytic activity.